Pendekatan Maqāṣīd al-Syarī'ah pada Tradisi Kawin Anak di Madura - Tatik Hidayati ('Anil Islam: Jurnal Kebudayaan dan Ilmu Keislaman, 2017)
This research aims to explain the importance of maqāṣīd al-syarī'ah approach in the case of child marriage that is growing in Madura. So far, the approach used in looking at the issue of child marriage is still textual. Precisely, fiqh used as legitimacy to preserve child marriage, yet the reality shows that child marriage is quite alarming. In this research, maqāṣīd al-syarī'ah as a method or ijtihād to uncover universal humanitarian goals in establishing law for human welfare, and also as a solution to reduce child marriage in Madura. The maqāṣīd al-syarī'ah approach in the provisions of Islamic law is an effort to reconstruct women's rights from the loss of knowledge, the right to health, the right of justice, and the right to gender equality. The results of this research showed as an alternative in preventing and give understanding and awareness to Muslims about the legal context of child marriage.